SCOPE OF THE SEARCH AND ACKNOWLEDGMENT OF THE INFRINGEMENT OF THE DUTY OF FITNESS IN THE CONSUMER JUSTICE IN PERU - Damián Medina, Omar Alfredo (2022)
This research will analyze the scopes ofthe acceptance and the recognition of the administrative liability of the supplier in the framework of an administrative proceeding against the infringement of the duty of suitability, from the insertion of new legal bodies that redirected the practice of the system of consumer protection and defense in Peru. Consequently, our purpose will be developed under a normative, hermeneutic and jurisprudential approach, from the evaluation of the various pronouncements of the Specialized Chamber on Consumer Protection of Indecopi in the period from 2012 to 2021.